Research Progress of Adsorption and Photocatalysis of Formaldehyde on TiO2/AC - Xinwei Zhu; Denghui Wang; Shien Hui (Adsorption Science & Technology)
Based on the increasingly serious formaldehyde pollution, effective degradation of formaldehyde has become a practical problem that humans urgently need to solve. Among many treatment methods, activated carbon has the advantages of large specific surface area, high adsorption efficiency, and uniform pore size distribution. As a kind of clean photocatalytic material for formaldehyde degradation, titanium dioxide supported by activated carbon has become a research hotspot to develop adsorption-catalytic materials for formaldehyde degradation. In this paper, the research progress of activated carbon and its modification, the photocatalytic principle and modification of titanium dioxide, and TiO2/AC materials are reviewed. The results show that the pore size distribution gradient and acidic oxygen-containing functional groups of activated carbon play key roles in the formaldehyde adsorption process. TiO2 doped with metal ions and nonmetal ions can significantly improve the photocatalytic activity. The TiO2/AC material can greatly improve the photocatalytic rate and achieve the technical goal of efficient and clean degradation for formaldehyde.